Sustainable Energy and Climate Strategies: lessons from planning processes in five municipalities. (1st July 2015) - Fenton, P.; Gustafsson, S.; Ivner, J.; Palm, J.
Abstract: Swedish municipalities have traditionally had significant powers and played a major role in implementing national energy strategies. This paper describes the factors influencing development of municipal climate and energy plans in five Swedish municipalities and assesses the relevance and importance of these factors from theoretical and practical perspectives. The questions raised in the paper are: what are the characteristics of municipal climate and energy planning processes in the five municipalities, do these municipalities include stakeholders in the process, if so how? Results suggest that a number of factors influence the development of municipal climate and energy strategies and their content. These include the importance of a clear, shared vision and engaged politicians; the size and organisational structure of the municipality and its willingness and capability to act; the organisation of the process and extent to which stakeholders have been involved; the need for clarity about financial aspects, such as planned financing of implementation; and the need for greater clarity concerning selection of targets and their relevance to global climate and energy trends. The study and its results may be used to inform policy-makers on the national and local levels about factors influencing municipal energy planning and also contribute to a discussion on benefits and problems of involving stakeholders and citizens in the strategic work to reduce climate impacts and energy consumption. Highlights: Study of strategic planning processes in five Swedish municipalities. Analysis of processes to develop energy and climate strategy. Choice of organisation and methods in planning process has profound implications on scope and content. Early and systematic involvement of stakeholders widens the scope of planning processes. Project financing and person-dependency creates uncertainty.